Simulated consult and treatment exercise improves radiation oncology trainee confidence and knowledge - Luca F Valle; Palak Kundu; Stephanie M Yoon; J Daniel Pennington; Minsong Cao; Percy P Lee; Amar U Kishan (Wolters Kluwer Medknow Publications, 2021)
Malignant epidural spinal cord compression (MESCC) represents the most common indication for emergent radiotherapy. First-year residents must quickly gain competence in managing this condition prior to taking call for the department. We sought to develop a hybrid didactic/simulation exercise to assist first-year radiation oncology residents in developing a skillset relevant to treating a MESCC case in an emergency situation. This was a prospective, qualitative survey study conducted at the University of California, Los Angeles, during the years 2014-2016. Following an introductory lecture during orientation for academic years 2014-2016, residents completed a simulated consultation on a patient with suspected MESCC. Subsequently, they worked with radiation therapists to complete the clinical treatment procedure (including field placement and manual calculation of monitor units needed to deliver the prescribed dose) to a phantom placed on a linear accelerator. Residents were then surveyed about whether the exercise increased confidence in their ability to successfully complete a consult, and urgent treatment if needed, for MESCC. All residents agreed or strongly agreed that this exercise had improved this ability, and all agreed or strongly agreed that the exercise was valuable and should be retained in the curriculum. Simulated consultation and treatment of MESCC provides new residents with increased confidence and knowledge regarding this relatively common indication for emergent radiation.